2017
DOI: 10.5191/jiaee.2017.24303
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Farm Visits on Farmers’ Satisfaction with Extension: Examining the Dependence on Individual Methods in the Caribbean

Abstract: This research sought to investigate the dependence on farm visits in selected Caribbean islands, and estimate the impact of such visits on farmers’ satisfaction with extension. The study utilized a causal-comparative design using a convenience sample from six major farming countries in the Eastern Caribbean. Descriptive frequencies, ANOVA, principal factor analysis, and hierarchical OLS regression models were presented. It appears the low use of alternate approaches to disseminate information to eastern Caribb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…Furthermore, many Extension officers who were not using ICTs were willing to use multimedia messaging, SMS, email, voice calls, and social media to interact with farmers. Past studies indicated a reliance on top-down extension models in the Caribbean (Ganpat et al, 2017;Ganpat, Ragbir, & de Freitas, 2010;Renwick, 2010). Now, it appears Ministry Extension officers are generally willing to use several forms of modern ICTs, including SMS, to communicate with farmers.…”
Section: Censusmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, many Extension officers who were not using ICTs were willing to use multimedia messaging, SMS, email, voice calls, and social media to interact with farmers. Past studies indicated a reliance on top-down extension models in the Caribbean (Ganpat et al, 2017;Ganpat, Ragbir, & de Freitas, 2010;Renwick, 2010). Now, it appears Ministry Extension officers are generally willing to use several forms of modern ICTs, including SMS, to communicate with farmers.…”
Section: Censusmentioning
confidence: 99%
“…However, with an Extension-to-farmer ratio of 1:600 and reliance on top-down extension methods and traditional information dissemination techniques, the Ministry Extension struggles to provide adequate services to Trinidadian farmers (Ganpat, Webster, & Narine, 2014;Ram, Ganpat, & Narine, 2017;Seepersad, 2003). The adoption of modern extension approaches is essential to addressing the needs of Trinidad's farmers (Ganpat, Narine, & Harder, 2017;Ganpat, Ragbir, & de Freitas, 2010;Renwick, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ministry Extension uses a variety of communication methods to serve farmers including farm visits, farmer training programs, short agricultural courses, demonstration farms, exhibitions, information dissemination units, and agricultural administrative services (Ganpat, 2013;Parker, 2016). Ganpat et al (2017) found Trinidadian farmers were less dependent on the Ministry Extension compared to other small islands of the eastern Caribbean region. Public-assisted organizations, input suppliers, non-governmental organizations, and research institutions are also key players in the Extension system of Trinidad and Tobago (Dolly, 2009;Ganpat et al, 2017;Ramjattan, 2017;Seepersad & Ganpat, 2008).…”
Section: Introductionmentioning
confidence: 92%
“…Extension providers aim to meet the needs of small-scale farmers in an effective and efficient manner (World Bank, 2017). While the Extension Service of the Ministry of Agriculture, Land and Fisheries (henceforth referred to as Ministry Extension) is the main provider of extension in Trinidad, farmers benefit from a pluralistic extension system (Ganpat, Narine, & Harder, 2017). The Ministry Extension uses a variety of communication methods to serve farmers including farm visits, farmer training programs, short agricultural courses, demonstration farms, exhibitions, information dissemination units, and agricultural administrative services (Ganpat, 2013;Parker, 2016).…”
Section: Introductionmentioning
confidence: 99%